Performance of Mulberry Silkworm (Bombyx mori L.) under Leaf and Shoot Feeding Methods - Thapa, RB; Ghimire, NP (Journal of the Institute of Agriculture and Animal Science, 2005)
Two batches of newly hatched J12 x C12 strain worms were reared in two separate trays feeding one with succulent Kanva-2 mulberry twigs and another with soft and tender chopped leaves of the same mulberry variety up to third molt. Then after, 200 worms per tray with six replications were fed on leaf and shoot separately throughout the larval period including combinations of leaf and shoot feeding to young and grown up instars. The result indicated that shoot feeding and its inclusion to leaf feeding were significantly better giving encouraging results (41.76 kg cocoon/box) and high remunerative return (Rs. 7295/box) compared to leaf feeding (38.56 kg cocoon/box) and earning (Rs. 6705.28/box), respectively. Key words: Mulberry silkworm, leaf vs shoot feeding, larval duration, shell ratio, cocoon yield J. Inst. Agric. Anim. Sci. 26:83-86 (2005)